The Gendering of Vulnerability and Protection Needs: Iraqi male refugees - Fernandez, Karin (AUC Knowledge Fountain, 2009)
Refugees pass through various stages from preflight, flight to post flight. It is argued that refugees as a whole - regardless of gender, race or ethnicity - should be considered vulnerable due to their actual or fear of persecution, but this is not always the case. This thesis looks at the ways in which the interpretation of “vulnerability” in the principles and practice of humanitarian aid in the refugee regime is affecting male Iraqi refugees seeking protection, resettlement and rehabilitation. As part of the evidence for this argument, the thesis examines gender differentials in the death rates and levels of violence affecting both Iraqi males and females in Iraq, the willingness of countries to take male Iraqi refugees and the level of protection these countries are willing to grant. Also under examination are the social services for rehabilitation, restitution and legal justice of male survivors of violence and sexual torture. It is argued that, because these experiences are minimized in male cases, further harm is brought to those survivors. The purpose of the thesis is to show the ways in which the restricted interpretation of vulnerability is applied transitionally through each of the stages of pre-flight, flight and post flight. In particular, attention is drawn to the low levels of protection given to Iraqi male refugees and the ramifications for both them and their families. It is argued that gendered concepts of vulnerability have become so ingrained into the social consciousness that humanitarian work, medical services, international law and academic scholars have continued to reproduce a gendered discourse that has become detrimental to a particular category of refugee, namely males.